EXPLORING CHRISTIAN LEADERSHIP IN PARACHURCH ORGANISATIONS IN LESOTHO - J.M. Morenammele; W.J. Schoeman (Acta Theologica)
The article explores authentic Christian leadership, as it applies to workplaces of parachurch organisations in Lesotho. The leadership of parachurch organisations have a responsibility to transform society through the influence they can exert on their employees. A qualitative methodology was used that involved interviews with ten chief executive officers and ten focus-group interviews from ten parachurch institutions based in the Maseru district, Lesotho. The theoretical framework and empirical analysis propose a leadership strategy that pays attention to servant leadership and team leadership that peruse an open and inclusive communication strategy. The empirical analysis indicates that leadership, through a competent and ethical example, is an essential dimension of authentic leadership in the workplace. Christians holding leadership positions in parachurch organisations must have strong intentions if they hope to influence and impact on the workplace for God and become the answer to the problems facing Lesotho.